Tingkat Pemahaman Guru MI Terhadap Penerapan Pembelajaran Saintifik - Agustina, Neli (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
Effort which began at the elementary school level, then encouraged the implementation of an active learning approach at the secondary school level. The results of these efforts were gradually integrated into the 1984 Curriculum, the 1994 Curriculum, and the 2004 Competency-Based Curriculum, which was followed by the Content Standards which are better known as the 2006 Educational Unit Level Curriculum (KTSP) (Mushfiqon and Nanda, 2015) ..The scientific approach is a learning model that provides space for students to explore and elaborate on the material being studied. Apart from that, this education model also provides students with the opportunity to hone their abilities through learning activities that have been designed by the teacher (Rusman, 2015). The scientific approach method is a learning and learning process that is designed in such a way that students actively construct concepts and laws through manifestation in various stages of observing (to identify or find problems), formulating problems, formulating hypotheses, collecting data using various techniques, analyzing data, draw conclusions, and communicate the concepts, laws or principles found (Karar and Yenice, 2012).